Left ventricular volumes at baseline and outcome in heart failure patients undergoing cardiac resynchronization therapy. (25th November 2020) - Kostyukevich, M; Van Der Bijl, P; Mertens, B; Vo, M; Marsan, N.A; Delgado, V; Bax, J.J
Abstract: Background: Studies evaluating the relationship between baseline left ventricular (LV) volumes and long-term prognosis in heart failure (HF) patients undergoing cardiac resynchronization therapy (CRT) are lacking. Purpose: To evaluate the association of LV end-systolic and end-diastolic volumes (ESV and EDV) with long-term prognosis in patients with HF treated with CRT. Methods: Patients from an ongoing institutional HF registry who received CRT according to contemporary guidelines were included. All patients underwent standard transthoracic echocardiography. LV volumes were measured using the biplane method during off-line analysis. Primary end-point included all-cause mortality, implantation of left ventricular assist device or heart transplantation, which were assessed according to the national death registry and case records. Results: In total, 1165 patients with feasible LV volume assessment were included (mean age 67±10 years; 74.8% males; 55.3% with non-ischemic aetiology of HF). After a median follow-up of 75 (40; 123) months, the primary end-point occurred in 708 (60.8%) patients. Median baseline LV ESV was 151 (108; 198) ml and EDV was 202 (156; 258) ml. All patients were divided into quartiles according to the baseline EDV and ESV: those with larger volumes were significantly younger, more frequently male and had longer QRS durations (p<0.001). Heart failure aetiology, glomerular filtration rate, quality of life and 6-minute walking test distance did not differ significantly between the groups (p>0.05). To investigate the association between long-term prognosis and baseline LV volumes (EDV and ESV), a Cox proportional hazards model was constructed with variables known to influence the mortality of HF patients (age, gender, aetiology, QRS duration, and estimated glomerular filtration rate). When separately included in a multivariate analysis, baseline LV ESV and LV EDV were both independently associated with the primary end-point (p<0.001). To demonstrate hazard change across the range of LV ESV and EDV as continuous variables, an adjusted (for covariates influencing HF mortality) spline curve was drawn, showing an increased mortality risk when the baseline LV ESV and EDV are larger than 100 ml and 200 ml, respectively (Figure). Conclusion: LV volumes before CRT implantation are independently associated with prognosis during long-term follow-up. Our findings indicate the importance of taking baseline LV remodelling into consideration to identify patients at high mortality risk after CRT implantation. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): The author acknowledges funding received from the European Society of Cardiology in form of an ESC Training Grant